Determinan Penggunaan Digital Payment dalam Pembayaran Wakaf Uang: Ekstensi Teori Technology Acceptance Model - Muhamad Fasya Nur Arbaien; Heni Sukmawati; Listia Andani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Indonesia has significant potential in developing the sharia economy, particularly in the cash waqf sector, despite its current low realization. This study explores the digitalization of cash waqf through e-wallets, crowdfunding, and shopping charity using the Technology Acceptance Model (TAM). A quantitative descriptive method with Smart PLS 3.0 analysis was applied to Muslim respondents in West Java who have used digital payment for cash waqf. The results indicate that perceived usefulness significantly influences attitudes and intentions, while perceived ease of use only impacts perceived usefulness. A positive attitude towards technology enhances the intention to use, thereby promoting the adoption of digital payment in cash waqf. Trust plays a crucial role in building user loyalty. The study implies the need to improve the quality of user interface (UI) and user experience (UX), transparency in fund management, and education on the benefits of digital payment to increase adoption and trust. Further research is recommended to explore digital literacy, government support, and employ longitudinal designs to understand changes in community attitudes and behaviors over time.